2021
DOI: 10.1136/rmdopen-2020-001228
|View full text |Cite
|
Sign up to set email alerts
|

Current view on the pathogenic role of anti-citrullinated protein antibodies in rheumatoid arthritis

Abstract: Epidemiological findings suggest a potential role for anti-citrullinated protein antibodies (ACPAs) in rheumatoid arthritis (RA) pathogenesis. ACPA-positive RA is associated with unique genetical and environmental risk factors, in contrast to seronegative RA. ACPA-positive healthy individuals are at risk of developing RA and can develop joint pain and bone loss already before disease onset. ACPA injection triggered bone loss and pain-like behaviour in mice and, in the presence of additional arthritis inducers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 76 publications
(81 reference statements)
0
48
0
2
Order By: Relevance
“…In the search for a potential mechanism underlying the SME modulation by ACPAs, we evaluated the potential involvement of FcR, previously reported to mediate the effects of these autoantibodies in leucocyte activation. 53 The blockage of FcR prevented the downregulation of SME induced by ACPAs, underlying the role of these receptors on such effects.…”
Section: Discussionmentioning
confidence: 97%
“…In the search for a potential mechanism underlying the SME modulation by ACPAs, we evaluated the potential involvement of FcR, previously reported to mediate the effects of these autoantibodies in leucocyte activation. 53 The blockage of FcR prevented the downregulation of SME induced by ACPAs, underlying the role of these receptors on such effects.…”
Section: Discussionmentioning
confidence: 97%
“…When NETs release a large amount of citrullinated antigens to drive ACPA production, the immune complexes containing ACPAs can form more NETs. Then, the immune complexes interact with the FCγ receptor (FCγR) on other neutrophils, releasing degrading enzymes and reactive oxygen species, ACPAs and citrullination promote programmed cell death, leading to autoantigen release ( 13 15 ) ( Figure 1 ). In RA patients' peripheral blood, ACPAs stimulate neutrophils to release PAD enzymes.…”
Section: Acpa Generationmentioning
confidence: 99%
“…After some additional arthritogenic triggers, citrulline-specific B cells may receive T cell help, inducing an inflammatory autoimmune response (“the second hit”) ( 32 ). Then, ACPA levels increase, antibody diversity expands, and the ACPA response matures ( 13 ).…”
Section: Acpas and Bone Destruction In Ramentioning
confidence: 99%
See 1 more Smart Citation
“… 8 These autoantibodies are thought to be pathogenic, because they might directly induce stimulatory signals by ligating key citrullinated cell surface molecules or, alternatively, act as immune complexes on Fc receptors. 98 A number of studies have revealed pathogenic processes to the onset of synovitis in RA, and production of RA autoantibodies precedes the onset of RA. 99 Specifically, in a genetically predisposed host, environmental insults, epigenetic modifications and post-translational modifications can lead to loss of immune tolerance with subsequent production of autoantibodies, including RF and ACPA.…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%